ANALISIS EKSPOR KERTAS TERHADAP PRODUK DOMESTIK BRUTO (PDB) INDONESIA TAHUN 2002-2015 - Tuty Nor Aminah; Syapsan Syapsan; Ufira Isbah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the Paper Export Analysis Against Gross Domestic Product (GDP) Indonesia in 2002-2015. This research is conducted with observation of annual paper export data, as well as reports of Gross Domestic Product (GDP) issued from the Central Bureau of Statistics, Indonesia. As well as observation reports from the Ministry of Trade and Ministry of Industry. The data used in this research is secondary data of annual time series from 2002-2015. Data analysis method used is simple regression analysis and multiple linear regression analysis with Ordinary Least Square (OLS) method using Eviews 9.0 program. This research uses one dependent variable that is Gross Domestic Product (GDP) and one independent variable that is paper export, for simple regression analysis then for multiple linear regression analysis this research uses one dependent variable that is Gross Domestic Product (GDP) and three independent variables ie Japan and the United States (As the two countries receiving paper export Indonesia.The result of the research from simple regression shows that simultaneously paper export variable has positive and significant effect to Indonesia Gross Domestic Product (GDP). The magnitude of the effect caused by one of these variables on the dependent variavel is 70%. The result of this research shows that simultaneously the paper export receiver variable to Japan has a positive and significant effect to Indonesia's Gross Domestic Product (GDP), then the recipient of paper export to the United States has a positive and significant effect on Gross Domestic Product (Gross Domestic Product) GDP) Indonesia. The magnitude of the effect of both these variables is attached to the dependent variable of 82%.Keywords: Paper Export, Gross Domestic Product (GDP)